ANALISIS KESIAPAN IMPLEMENTASI REKAM MEDIK ELEKTRONIK DI RUMAH SAKIT UNIVERSITAS BRAWIJAYA - Oktaviana, Savira Pratista (Jurnal Administrasi Publik, 2024)
Analysis of Readiness for Imolementation of Electronic Medical Records at Brawijaya University Hospital. The health sector is currently developing rapidly due to increasingly sophisticated information and communication technology. Electronic medical records in Indonesia are regulated through Minister of Health Regulation (PMK) Number 24 of 2022 concerning Medical Records. This policy requires health service facilities (fasyankes) to run an electronic patient health history recording system. This research aims to determine the readiness to implement electronic medical records at Brawijaya University Hospital. This research uses descriptive research with a total sample of 13 people. The analytical method used is the descriptive analysis method. Primary data collection was carried out using the adapted DOQ-IT questionnaire. The research results show that RSUB is quite ready to implement ESDM with a score of 80.17. Things that are not yet ready include finance, infrastructure and human resources. RSUB is quite ready, but improvements need to be made to be ready to implement electronic medical records.